THE ANALYSIS OF MAXIMS FOUND IN THE NOVEL “NEVER GO BACK”: THE ANALYSIS OF MAXIMS FOUND IN THE NOVEL “NEVER GO BACK” - I Putu Eka Suardana (Focus Journal : Language Review, 2022)
The novel Never Go Back is a best selling novel written by Lee Child. He is one of the world’s leading thriller writers. The novel is sold somewhere in the world every twenty seconds. The second Jack Reacher film starring Tom Cruise, based on this novel, is out in October 2016. It consistently achieves the number-one slot in hardback and paperback on bestseller lists on both sides of the Atlantic, and is published in over one hundred territories. He is the recipient of many prizes, most recently the CWA’s Diamond Dagger for writer of an outstanding body of crime fiction. He was born in Coventry, brought up in Birmingham, and now lives in New York. The uses of maxims are found in a number of utterances of the novel. The aim of the research is to analyze the uses of those ones in the novel’s utterances. They are maxim of quality, maxim of quantity, maxim of relation, and maxim of manner. The research method used in the research is qualitative method. According to Grice in Leech (1983: 7-8), there is a general assumption underpinning all utterances interpretations. The interpretation is guided by a cooperative principle, in which a speaker and a hearer are engaged in some shared goals. Then, the elements of those cooperative principles are called maxims. There are four kinds of maxims. Firstly, maxim of quality, it is meant that do not say what you believe to be false. You are not expected to say lack adequate evidence. Secondly, maxim of quantity, it requires your contribution as informative as is required. Thirdly, maxim of relation, it requires your contribution to be relevant. Fourthly, maxim of manner, it is meant that your contribution must be perspicuous and brief. It also avoids obscurity of expression and ambiguity. The aim of the study is: (i) to find out maxims in the novel, (ii) to classify the maxims, (iii) to analyze the kinds of each maxim.